Pixley Community Sign on Southbound Highway 99 - Watkins, Howard::::::::: (1988)
Sign says: PIXLEY--Home of the Pixley Nat'l Wildlife Refuge"; below it reads: "Lions Club Pheasant Hunt Nov. 14th thru. Dec.13th"